Analisis Strategi Perluasan Pemasaran Cabai di Kecamatan Baros Kabupaten Serang Provinsi Banten - Safitri, Ika; Aliudin, Aliudin; Aliah, Aliah; Imania, Renita; Dzikri, Rizka Febrina (CV.ITTC INDONESIA, 2025)
This study aims to analyze the marketing expansion strategy of chili commodities in Baros District, Serang Regency. The research employs a qualitative approach with data collected through in-depth interviews with four chili farmers as the primary respondents. Informants were selected using purposive and snowball sampling techniques. The interviews were conducted semi-structurally using open-ended question guides to explore information on marketing strategies, challenges faced, and steps taken to expand market reach. The results of the study indicate that the main challenges faced by farmers in expanding chili marketing in Baros District include price fluctuations, limited market access, lack of business capital, and insufficient support or assistance from the government in terms of financing and marketing support facilities. This research is expected to serve as a consideration for farmers and related stakeholders in formulating effective and sustainable marketing strategies.